Solution processable perovskite-hybrid heterojunction silicon 4T tandem solar cells - Mohammad Adil Afroz; Bhavna Sharma; Ruchi K. Sharma; Ritesh Kumar Gupta; Ankita Sengupta; Sanjay K. Srivastava; Soumitra Satapathi (Materials Today Advances)
Solar photovoltaic technology has witnessed significant advancements through the development of novel hybrid heterojunction solar cells (HHSCs). However, there is scope for enhancement of power conversion efficiency (PCE) of the HHSCs. Here, a solution-based fabrication approach involving a high-performance semi-transparent perovskite cell (ST-PSC) stacked in tandem with a hybrid heterojunction silicon solar cell (HHSC) has been demonstrated for efficiency enhancement. The proposed 4-terminal tandem architecture exploits light management through the bandgap matching of the perovskite cell with silicon to minimize thermalization and absorption losses. This has led to a significant 41 % enhancement in the PCE of the HHSC. The experimental results are also correlated with the help of SCAPS 1D simulation. These low cost tandem solar cells hold the potential for upscaling and commercialization.